2021
DOI: 10.35633/inmateh-63-36
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining “Organic Seeds” of Vegetable and Industrial Plants Using the Aerodynamic Properties of the Seeds

Abstract: The production and quality of any agricultural crop is determined both by the factors acting from the moment of sowing until harvesting, as well as by those that directly influence the seeds before sowing. In the organic cultivation of cereals, industrial plants, vegetables, medicinal plants, the seeds must be clean without any impurities because the maintenance of these crops does not allow using chemicals. There is a number of technologies and pieces of equipment for separating impurities. In case of separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results of the theoretical and experimental studies differed by about 10%. It was found that the intensity of the airflow as well as the method and velocity of seed mixture delivery in the separator working zone have the greatest influence on the separation of mixture components [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the theoretical and experimental studies differed by about 10%. It was found that the intensity of the airflow as well as the method and velocity of seed mixture delivery in the separator working zone have the greatest influence on the separation of mixture components [24].…”
Section: Introductionmentioning
confidence: 99%
“…The grain flow and the airflow velocity do not show a clear trend in the variation of airflow dispersion. [25] The quality of seed separation in this module depends on the uniformity and degree of stability of the airflow velocity in the field working area of the sorting chamber [24].…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of crop production, soil and environmental health is important [12]. Also the quality of any agricultural crop is determined by the factors that act from the moment of sowing to harvest [18].…”
Section: Introductionmentioning
confidence: 99%
“…The trend of superior capitalization of wine by-products has led to the development of various separation methods that use complex equipment, which includes in their components systems for prepreparation of the seed mixture before the actual separation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%